Znaczenie Internetu w zarządzaniu relacjami z klientem na rynku polskim - Pukas, Anetta; Żyminkowski, Tomasz (The Importance of Internet in Customer Relationship Management of the Polish Market, 2007)
The Internet's growth as an electronic medium and tool of commerce has brought tremendous changes in market competition, especially on the ED market. This article presents the impact of the Internet technology on CRM-area. From a marketing perspective, the Internet can be described.as a communication tool, customer service method, and selling way. On the other hand, the Internet can assist companies in tree ways: understanding customer behaviour, providing personalized services and requiring customer loyalty. The authors present characteristics and examples of the utilization of Internet technology in Polish and other European firms, where the CRM-philosophy is developed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 108-121